Kyphoplasty for thoracic and lumbar fractures with an intravertebral vacuum phenomenon in ankylosing spondylitis patients - Liu, Hao; Zhou, Quan; Zhang, Junxin; Deng, Lei; Hu, Xiayu; He, Wei; Liu, Tao; Yang, Huilin (Frontiers in Surgery, 2022)
Background: Intravertebral vacuum phenomenon (IVP) is a special sign after vertebral fractures, which is common in patients with ankylosing spondylitis (AS) and may indicate pseudarthrosis and bone nonunion that lead to spinal instability. The objective of this study is to evaluate the efficacy and safety of kyphoplasty (KP) in treating such type of vertebral fractures with AS. Methods: Sixteen patients with AS suffering from thoracic or lumbar fractures with IVP received KP from 2015 to 2020, and were followed up for more than 1 year. The visual analogue scale (VAS) score was used to evaluate back pain relief. The Oswestry Disability Index (ODI) questionnaire was used to assess improvement of the patients’ living quality. The anterior and middle vertebral height restoration ratio (AVH, MVH) and the kyphotic angle (KA) were used to evaluate the radiographic results. Results: The mean follow-up period was 20.8 months (12~28 months). The VAS and ODI significantly reduced at 3 days, 3 months after surgery and at last follow-up compared with the preoperative (p<0.05). The AVH and MVH were significantly increased compared with the preoperative (p<0.05). There was a significant correction in the KA between pre- and postoperative assessment (p<0.05). Asymptomatic intradiscal Polymethylmethacrylate (PMMA) cement leakage was found in two patients. Conclusions: For thoracic or lumbar fractures with IVP in AS patients, KP may be safe and effective which achieves pain relief and satisfied functional improvement, restores the anterior and middle height and corrects the kyphotic angle of fractured vertebra.